The Philosophy of Color in Malay Tradition Symbolism, and the Implementation of Cultural Values for Modern Society - Hasnah Faizah; Irwanto Irwanto; Ika Apriyanti; Putri Endang Kemalasari; Hendri Ramadhan (International Journal of Studies in International Education, 2026)
This study aims to comprehensively examine the profound philosophical values and moral messages deeply embedded within the traditional color conventions of Malay customs. The primary focus is to critically analyze the historical and contemporary use of color as a powerful "silent language" that intricately represents cultural identity, hierarchical social stratification, and sacred spiritual values within Malay society (Samsudin & Mohd Khidzir, 2020). To achieve this, the method employed is a qualitative descriptive research design, utilizing an ethnographic communication study approach combined with a meticulous cultural semiotic analysis. Data analysis was systematically conducted through data reduction techniques, semiotic analysis to thoroughly examine the relationship between the signifier and signified, as well as a humanistic interpretation aimed at connecting traditional color meaning with modern human values and ethics (Ariyaningsih et al., 2023). Ultimately, the findings reveal that color in Malay custom functions as a vital medium of non-verbal communication that seamlessly integrates moral and spiritual values for modern society under the guiding cultural principle of "Adat bersendi Syarak, Syarak bersendi Kitabullah" (Custom grounded in Islamic Law, Islamic Law grounded in the Holy Quran) (Effendy, 2006). This integration underscores how traditional aesthetics continue to preserve societal harmony, ethical standards, and profound spiritual devotion.